Malaria eradication within a generation: ambitious, achievable, and necessary - Feachem, Richard G A; Chen, Ingrid; Akbari, Omar; Bertozzi-Villa, Amelia; Bhatt, Samir; Binka, Fred; Boni, Maciej F; Singh, Balbir (Elsevier Ltd., 2019)
Where once the notion of malaria elimination at the regional level seemed beyond reach, the international discussion has now turned to an even loftier goal—the complete global eradication of malaria. Despite increased investment, technological improvements, and a massive reduction in deaths annually, arriving at consensus around the feasibility and the path to achieving malaria eradication has been difficult. The Lancet Commission on malaria eradication provides such a path. In the first report of its kind and with a bold vision, the Commission lays the out the necessary steps, including an even greater financial outlay, strengthening malaria programmes and global leadership, and acceleration of research and development, to eradicate malaria within a generation.